PENGEMBANGAN APLIKASI DATA MINING INFORMASI TINGKAT KELULUSAN MAHASISWA MENGGUNAKAN ALGORITMA APRIORI - Candra Adi Pranata, Gede; Mahendra Darmawiguna, I Gede; Windu Antara Kesiman, Made (Universitas Pendidikan Ganesha, 2014)
Good student graduation level is the desire of every University. In order to get a better graduation rate, understanding of the student’s value is needed. In this case, some of the issues related to the student will be examined to get a connection to the student’s graduation rate. This study aims to process the data in order to display the student parent relationship with graduation rates. Mining methods and algorithms priori are used in this study.Data mining method is a method which is used to process many data. The purpose of this method is to generate information from a priori algorithm. Priori algorithm is data retrieval algorithms using associative rules (Association rule) to determine the associative relationships of a combination of items. Association Rule is conducted through a calculation of the support and confidence of a relationship item. An association rule will be interesting if the value is greater than the minimum support and confidence value is greater than the minimum confidence.The result of this study is software called Application Graduation. Based on test result of the software, it was found that the Application Graduate student registration information could create relationship between data and student graduation rates.